2020
DOI: 10.1080/0284186x.2020.1736335
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in palliative care service full utilisation among patients with advanced cancer: a retrospective Cohort study

Abstract: Background: Advanced cancer patients often die in hospital after receiving needless, aggressive treatment. Although palliative care improves symptom management, barriers to accessing palliative care services affect its utilisation, and such disparities challenge the equitable provision of palliative care. This study aimed to identify which factors are associated with inequitable palliative care service utilisation among advanced cancer patients by applying the Andersen Behavioural Model of Health Services Use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous studies have also suggested that older patients are more likely to receive palliative care. 30-32 However, Janah et al reported that younger cancer patients aged 18-49 were more likely to receive palliative care. 33 Regardless, there is evidence of benefit when palliative care is offered to patients early on in their disease rather than at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that older patients are more likely to receive palliative care. 30-32 However, Janah et al reported that younger cancer patients aged 18-49 were more likely to receive palliative care. 33 Regardless, there is evidence of benefit when palliative care is offered to patients early on in their disease rather than at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Health inequities exist on several fronts, 7 8 including decreased access to preventative medicine, 9 higher burden of disease 3 and poorer access to assessment and treatment 10 as well as palliative care. 11 Similar trends are apparent within eyecare. [12][13][14][15] Black and Latinx people in the USA are less likely than white people to report having visited an eye care provider.…”
Section: What Are the New Findings?mentioning
confidence: 61%
“…This study was in agreement with the Italian study and Zimbabwe. In Italy, patients were more likely to use palliative care services if they lived less than 20 km from a facility that provided specialist palliative care [ 30 ]. Patients in Zimbabwe, who lived in closed distance from radiotherapy facilities had a higher likelihood of receiving palliative radiotherapy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%